Hubungan Persepsi Pola Asuh Otoriter dengan Pengambilan Keputusan Karir pada Mahasiswa - Tantra, Muhammad Raihan; Malahati, Fildzah (EduInovasi: Journal of Basic Educational Studies, 2025)
This study seek to ascertain the correlation between the perception of authoritarian parenting perception and career decision-making in college students. 100 enrolled college students participated in this quantitative study, which used a correlational methodology. The Authoritarian Parenting and the Career Decision-Making Scale were used to collect the data. The study's findings demonstrated a strong positive correlation between vocational decision-making and authoritarian parenting. With a Pearson correlation value of 0.238 and a significance level of 0.017 (<0.050), it shows that the higher the child's perception of the authoritarian parenting pattern of parents, the higher their career decision-making will be. Through this study, further researchers are advised to specifically select students who have a perception that their parents are apply an authoritarian parenting when determining respondents.